LO43: First Nations emergency care visits in Alberta: Descriptive results of a retrospective cohort study. (May 2020) - McLane, P.; Barnabe, C.; Holroyd, B.; Colquhoun, A.; Bill, L.; Fitzpatrick, K.; Rittenbach, K.; Healy, C.; Bull, H.; Crawler, M.; Firth, L.; Jacobs, T.; et al.
Abstract : Introduction: Emergency care serves as an important health resource for First Nations (FN) persons. Previous reporting shows that FN persons visit emergency departments at almost double the rate of non-FN persons. Working collaboratively with FN partners, academic researchers and health authority staff, the objective of this study is to investigate FN emergency care patient visit statistics in Alberta over a five year period. Methods: Through a population-based retrospective cohort study for the period from April 1, 2012 to March 31, 2017, patient demographics and emergency care visit characteristics for status FN patients in Alberta were analyzed and compared to non-FN statistics. Frequencies and percentages (%) describe patients and visits by categorical variables (e.g., Canadian Triage Acuity Scale (CTAS)). Means and standard deviations (medians and interquartile ranges (IQR)) describe continuous variables (e.g., distances) as appropriate for the data distribution. These descriptions are repeated for the FN and non-FN populations, separately. Results: The data set contains 11, 686, 288 emergency facility visits by 3, 024, 491 unique persons. FN people make up 4.8% of unique patients and 9.4% of emergency care visits. FN persons live further from emergency facilities than their non-FN counterparts (FN median 6 km, IQR 1-24; vs. non-FN median 4 km, IQR 2-8). FN visits arrive more often by ground ambulance (15.3% vs. 10%). FN visits are more commonly triaged as less acute (59% CTAS levels 4 and 5, compared to non-FN 50.4%). More FN visits end in leaving without completing treatment (6.7% vs. 3.6%). FN visits are more often in the evening – 4:01pm to 12:00am (43.6% vs. 38.1%). Conclusion: In a collaborative validation session, FN Elders and health directors contextualized emergency care presentation in evenings and receiving less acute triage scores as related to difficulties accessing primary care. They explained presentation in evenings, arrival by ambulance, and leaving without completing treatment in terms of issues accessing transport to and from emergency facilities. Many factors interact to determine FN patients' emergency care visit characteristics and outcomes. Further research needs to separate the impact of FN identity from factors such as reasons for visiting emergency facilities, distance traveled to care, and the size of facility where care is provided.